Acute pancreatitis in the older patient: Is a new risk score required?. (August 2021) - Bath, Michael F; Som, Robin; Curley, Daniel; Kerwat, Rajab
Introduction: The average age of the surgical patient in the UK is increasing. Frailty and cognitive impairment have been shown to be important risk factors in elderly patients with surgical pathology. Limited work has previously assessed the outcomes of acute pancreatitis in the elderly population and the usefulness of current severity scoring methods. We aimed to assess the mortality rates in this cohort and identify any factors that may influence patient outcome. Methods: All patients ≥ 80 years admitted with acute pancreatitis between 1 January 2014 and 31 May 2018 were retrospectively identified. Disease severity scores were measured by a modified Ranson score, and patients' co-morbidities were quantified with the Charlson Comorbidity Index. Primary endpoint was whether the patient was alive at discharge; multilevel logistic regression was used to identify any independent risk factors for patient outcomes. Results: Eighty-seven patients were included, with an average age of 86 years. The most common aetiology was gallstones. Nine patients died during admission, and ITU admission was the only predictor of mortality (p = 0.027). Twenty-three patients had died by one year. Endoscopic retrograde cholangiopancreatography was more common in patients with gallstone disease who were alive at one year (p = 0.029). Discussion: Risk severity and co-morbidity scores are not predictive of outcomes in elderly patients with acute pancreatitis. The use of endoscopic retrograde cholangiopancreatography should be considered in elderly patients with acute gallstone pancreatitis where suitable. Further work is needed to identify improved mortality prediction tools in the elderly with acute pancreatitis and optimal management strategies.